Exploring the use of collaborative autoethnography as a tool for facilitating the development of researcher reflexivity. (April 2022) - Miyahara, Masuko; Fukao, Akiko
Abstract: This study explored the experiences of two practitioner researchers engaged in qualitative research at a Japanese university, by employing the collaborative autoethnographic-oriented approach (CAE). Drawing on data from a previous longitudinal research on learner autonomy, the methodological aspect of the research was reflected upon by focusing on the interview process, in an attempt to explore how CAE could function as a tool for further professional development. Drawing upon the iterative nature of the reflexivity (Chang et al., 2013; Finlay, 2012; Mann & Walsh, 2017), the data collection process involved cycles of individual meta-reflections on the diaries maintained in the previous study, and audio recorded face-to-face discussions of the pre and post-dialogue reflective writings of the researchers. The dialogic accounts strengthened the researchers' understanding of how they were connected to the research context both on micro and macro levels, and how these two dimensions intertwined to provide new meanings to their sense of self, experiences, and knowledge building. On the basis of the discussion it was concluded that CAE performs dual functions: it is not only a research methodology but can also serve as an effective tool for promoting professional development of researchers through reflexivity.